Writing proficiency as focus of expressive and integrated language teaching approaches - Florece, Evelyn Enverga (2006)
The purpose of this investigation was to establish the effects of Expressive and Integrated Approaches in English language teaching in the writing proficiency of freshman college students. Sixty college freshmen were the subjects. The data were obtained from the language competence and the writing proficiency pre and posttests of the subjects. It was revealed that there was a significant relationship between language competence and writing proficiency of both groups and that gender and writing proficiency showed a degree of relatedness. It was then recommended that there should be a balance in the use of the two English language teaching approaches, the form approach (Expressive) and the meaning-focused approach (Integrated).
"May 2006."
Thesis (Ph.D. Language Education)--University of the Philippines, Diliman.
Keywords: English language -- Study and teaching (Higher) -- Philippines -- Quezon City; English language -- Writing -- Study and teaching -- Philippines -- Quezon City; English language -- Ability testing -- Philippines -- Quezon City